2015
DOI: 10.1177/0956462415579589
|View full text |Cite
|
Sign up to set email alerts
|

Using Elecsys® HIV Combi PT assay to identify acute and early HIV infection in a teaching hospital of southwest China

Abstract: This study is the first attempt to evaluate the use of the Elecsys® HIV combi PT assay in identifying acute and early HIV infection in southwest China. We also analyzed the extent of cutoff ratios overlap between false-positive and true-positive results to aid the identification of HIV infection, using samples from the West China Hospital in Chengdu, Sichuan Province from April 2012 to December 2013. Reactive results from a screening test were retested and all repeatedly reactive samples - if available - were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The Elecsys HIV combi PT assay (the fourth‐generation assay) was used for screening HIV infection on Cobas e601 or Modular E170 analyzer (Roche Diagnostics, Mannheim, Germany) 14 . All initially positive (cut‐off index [COI] > 1.0) or borderline (0.9 ≤ COI ≤ 1.0) specimens were retested by the third‐generation Anti‐HIV enzyme‐linked immunosorbent assay kit (Zhuhai Livzon Diagnostics Inc, Zhuhai, China) on Freedom EVOlyzer (Tecan, Switzerland) 14 before June 2016, or by the third‐generation Anti‐HIV Colloidal gold kit (Zhuhai Livzon Diagnostics Inc) after June 2016. Western Blot (WB) HIV blot 2.2 (MP Diagnostics, Singapore) was recommended as a confirmatory test 14 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Elecsys HIV combi PT assay (the fourth‐generation assay) was used for screening HIV infection on Cobas e601 or Modular E170 analyzer (Roche Diagnostics, Mannheim, Germany) 14 . All initially positive (cut‐off index [COI] > 1.0) or borderline (0.9 ≤ COI ≤ 1.0) specimens were retested by the third‐generation Anti‐HIV enzyme‐linked immunosorbent assay kit (Zhuhai Livzon Diagnostics Inc, Zhuhai, China) on Freedom EVOlyzer (Tecan, Switzerland) 14 before June 2016, or by the third‐generation Anti‐HIV Colloidal gold kit (Zhuhai Livzon Diagnostics Inc) after June 2016. Western Blot (WB) HIV blot 2.2 (MP Diagnostics, Singapore) was recommended as a confirmatory test 14 .…”
Section: Methodsmentioning
confidence: 99%
“…All initially positive (cut‐off index [COI] > 1.0) or borderline (0.9 ≤ COI ≤ 1.0) specimens were retested by the third‐generation Anti‐HIV enzyme‐linked immunosorbent assay kit (Zhuhai Livzon Diagnostics Inc, Zhuhai, China) on Freedom EVOlyzer (Tecan, Switzerland) 14 before June 2016, or by the third‐generation Anti‐HIV Colloidal gold kit (Zhuhai Livzon Diagnostics Inc) after June 2016. Western Blot (WB) HIV blot 2.2 (MP Diagnostics, Singapore) was recommended as a confirmatory test 14 . HIV‐1 p24 antigens were detected by the Elecsys HIV Ag immunoassays on a Cobas e601 analyzer, while HIV‐1 RNA results were collected from the hospital laboratory information system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FP results usually generate LP&E S/CO signals as seen by other centres [2,6,7]. Using a combination of independent sample testing and different platform testing, for confirmation, we found that 85% of LP&E results were FP and therefore, LP&E result prevalence can be used as an indicator of FP rate.…”
Section: Discussionmentioning
confidence: 54%
“…Setting-appropriate and conservative cut-offs: The manufacturer regards a signal/sample cut-off (S/CO) > 1 as positive (4). However, based on local verification and data from other sites, a S/CO from 0.9-3) is regarded as equivocal (E), 3-30 as low positive (LP) and � 30 as positive (P) [6].…”
Section: Discussionmentioning
confidence: 99%